2014
DOI: 10.1186/2191-219x-4-12
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring tumour response during chemo-radiotherapy: a parametric method using FDG-PET/CT images in patients with oesophageal cancer

Abstract: BackgroundThe objective of this study is to investigate the feasibility and the additional interest of a parametric imaging (PI) method to monitor the early tumour metabolic response in a prospective series of oesophageal cancer patients who underwent positron emission tomography with fluoro-2-deoxy-d-glucose (FDG-PET/CT) before and during curative-intent chemo-radiotherapy.MethodsFifty-seven patients with squamous cell carcinoma (SCC) of the oesophagus prospectively underwent FDG-PET/CT before chemo-radiother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Comparisons between cancer metabolism revealed by PET-CT before and after treatments enables evaluation of responses to treatments (6,24,25). Previous studies reported that decreases of standardized uptake value in tumors evaluated by PET-CT after preoperative chemoradiotherapy were associated with histopathological tumor responses (26,27). Moreover, PET-CT performed after CRT predicted the prognoses of patients with primary or postoperative recurrent EC (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons between cancer metabolism revealed by PET-CT before and after treatments enables evaluation of responses to treatments (6,24,25). Previous studies reported that decreases of standardized uptake value in tumors evaluated by PET-CT after preoperative chemoradiotherapy were associated with histopathological tumor responses (26,27). Moreover, PET-CT performed after CRT predicted the prognoses of patients with primary or postoperative recurrent EC (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of relative changes on a voxel level is unreliable for tumor subvolumes with a very low baseline PET value, for which relative changes may be high despite both baseline and posttherapy PET image values within the background range. Evaluation of absolute change in PET values on a voxel level (129,130) might be less sensitive to cases of very low baseline PET values. An evaluation of the therapeutic response on a voxel level is also strongly affected by the selection of registration algorithm (131).…”
Section: Spatially Resolved Treatment Response Evaluationmentioning
confidence: 99%
“…An obvious approach to incorporate the intratumoral heterogeneity into treatment response would be to evaluate spatial therapeutic response. Therapeutic response can be evaluated at a voxel level as absolute change in the PET values (129,130) or as relative change from the baseline image (131). Evaluation of relative changes on a voxel level is unreliable for tumor subvolumes with a very low baseline PET value, for which relative changes may be high despite both baseline and posttherapy PET image values within the background range.…”
Section: Spatially Resolved Treatment Response Evaluationmentioning
confidence: 99%
“…It preserves the topology of the anatomical structures by allowing only rotations and translations in the transformation. Although rigid registration is straightforward, it has been shown to achieve good alignment between baseline and evaluation scans in tumour response assessment studies 12,[16][17][18][19] (Table 1). Necib et al 12 reported their study in metastatic colorectal tumour response assessment using PET/CT scans acquired before and during CTx.…”
Section: Rigid Registrationmentioning
confidence: 99%
“…The changes of comprehensive spatial temporal features from 18 F-FDG-PET scans were found to be useful for the assessment of response to CRT. Vera et al 19 applied similar rigid registration to align baseline and mid-therapy 18 F-FDG-PET/CT scans to monitor the early tumour metabolic response to CRT of patients with oesophageal cancer. The results showed that the changes in 18 F-FDG uptakes provided prognostic information for the early tumour metabolic response.…”
Section: Rigid Registrationmentioning
confidence: 99%